Institutional Publication Pressure and Perceived Epistemic Injustice: Mediating Roles of Cost Privatization and Research Cannibalization in Indonesia - Ahmad Erza; Dais Susilo; Gladys Putri (HM Publisher, 2026)
Background: The transition of scholarly publishing from a subscription model to an article-processing-charge (APC) model has reorganized the political economy of knowledge production, yet researcher-level perceptions of its fairness remain under-measured in the Global South. Objective: Drawing on academic-capitalism and epistemic-injustice theory, this study examined whether institutional publication pressure predicts perceived epistemic injustice, and whether publication-cost privatization and research cannibalization mediate that relationship, among academics at a public organization in Palembang, South Sumatera, Indonesia. Methods: A cross-sectional survey was administered to 312 academics using validated multi-item Likert scales. Reliability, a correlation matrix, multiple regression, parallel mediation with 5,000-sample bootstrap intervals, moderation, Harman’s single-factor test, and variance inflation factors were computed. Results: All constructs were reliable (Cronbach’s α = 0.78–0.83). Institutional publication pressure (β = 0.219, 95% CI [0.116, 0.321], p < 0.001), publication-cost privatization (β = 0.298, 95% CI [0.201, 0.396], p < 0.001), and research cannibalization (β = 0.293, 95% CI [0.196, 0.390], p < 0.001) each independently predicted perceived epistemic injustice, explaining 34.6% of its variance (F = 54.38, p < 0.001). Both mediators carried significant indirect effects (via privatization 0.111, 95% CI [0.068, 0.163]; via cannibalization 0.105, 95% CI [0.064, 0.151]), indicating partial parallel mediation. Perceived grant availability moderated the pressure-to-privatization path (interaction β = −0.145, p = 0.006). Common method bias was not serious (Harman’s single factor = 33.3%). Conclusion: Findings formalize the “illusion of inclusivity” as a measurable perception and suggest that publication mandates unaccompanied by adequate funding generate perceived epistemic injustice in Indonesian public institutions.